Perkembangan Sistem Pendidikan Nasional Indonesia - Titony Tanjung; Bermawi Nasution; Ridwal Trisoni (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
As time goes by, the education system in Indonesia dynamically follows the times. This development can be seen from changes in the current learning curriculum. Education plays an important role in determining the future of a nation. The Indonesian education system that applies nationally functions to develop students' abilities. In this case, the education system acts as a means to improve students' intellectual, physical and emotional abilities so that they are able to contribute to nation building. National education is education based on Pancasila and the 1945 Constitution of the Republic of Indonesia which is rooted in religious values, Indonesian national culture and responsive to the demands of changing times. Indonesia has its own national education system which implements 12 years of compulsory education, namely nine years of basic education which includes six years in elementary school and three years each in middle school and high school